2009
DOI: 10.1038/ajg.2009.300
|View full text |Cite
|
Sign up to set email alerts
|

DNA Promoter Hypermethylation of p16 and APC Predicts Neoplastic Progression in Barrett's Esophagus

Abstract: Introduction Prediction of progression to cancer in patients with Barrett’s esophagus is difficult using current techniques. We determined whether DNA promoter hypermethylation of genes frequently methylated in esophageal adenocarcinoma (p16 and APC) could be used as predictors of progression in Barrett’s esophagus. Methods We first performed a cross-sectional study to evaluate the prevalence of gene hypermethylation in biopsies from patients with normal esophagus (n=17), Barrett’s esophagus (n=102), and ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 45 publications
3
74
1
1
Order By: Relevance
“…Aberrancy of p16, such as mutations, methylations and deletions, are some of the earliest events in cancer (16). P16 is also involved in the pathogenesis of EAC with a number of P16 alterations such as gene locus loss, LOH (loss of heterozygosity), mutations and methylation being present in BE, the pre-malignant stage of EAC (17)(18)(19)(20) and consequently increasing with increasing tissue dysplasia (17,18,20). In a number of cancers it has been shown that aberration of p16 affect phosphorylation status of Rb (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Aberrancy of p16, such as mutations, methylations and deletions, are some of the earliest events in cancer (16). P16 is also involved in the pathogenesis of EAC with a number of P16 alterations such as gene locus loss, LOH (loss of heterozygosity), mutations and methylation being present in BE, the pre-malignant stage of EAC (17)(18)(19)(20) and consequently increasing with increasing tissue dysplasia (17,18,20). In a number of cancers it has been shown that aberration of p16 affect phosphorylation status of Rb (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Hypermethylation (an increase in the methylation) of p16 gene promoter is present at a much higher frequency in BE with dysplasia and EA than in Barrett's intestinal metaplasia (25, 38, 40 -41). Detection of p16 hypermethylation may be used to predict the neoplastic progression (24,38). Therefore, hypermethylation of p16 gene promoter is an important mechanism inactivating p16.…”
mentioning
confidence: 99%
“…Alternative mechanisms like p16 promoter methylation or p16 gene mutation could be the reasons for loss of p16 protein expression in this case. Methylation of p16 promoter is considered as common mechanism of p16 gene derailment during molecular pathogenesis of EAC, whereas p16 gene mutation is less probable [15,36,37,38,39]. It is plausible also that very small deletion of p16 could occur, which does not delete the entire LSI p16 probe target and consequently cannot be detected by FISH technique.…”
Section: Discussionmentioning
confidence: 99%